Oxovanadium(IV) complexes bearing substituted pentane-2,4-dionate ligands: Synthesis, structure and drying activity in solvent-borne alkyd paints - Preininger, Ondřej; Charamzová, Iva; Vinklárek, Jaromír; Císařová, Ivana; Honzíček, Jan (My University, 2017)
New oxovanadium(IV) pentane-2,4-dionate complexes decorated with long alkyl tails have been prepared and characterized by the spectroscopic methods and the X-ray crystallography. The increased solubility in non-polar organic solvents enabled to investigate the catalytic activity of the title compounds on various solvent-borne alkyd resins. The detailed study of the drying process reveals their excellent performance at considerably lower concentrations than usual for commertial cobalt-based driers. Furthermore, the oxovanadium(IV) compounds are highly active in wider range of concentration. Such lower sensitivity to precise dosage helps to avoid the overdose effect without necessity of other additives.
Oxovandičité komplexy se substituovanými pentan-2,4-dionatovými ligandy: Příprava, struktura a sikativační aktivita v rozpouštědlových alkydových nátěrových hmotách
Keywords: Vanadium; Acetylacetonate; X-ray structure; Alkyd paints; Autoxidation; Vanad; acetylacotonát; RTG-struktura; alkyd; autooxidace